2005
DOI: 10.1523/jneurosci.2727-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Inositol 1,4,5-Trisphosphate-Dependent Ca2+Threshold Dynamics Detect Spike Timing in Cerebellar Purkinje Cells

Abstract: Large Ca2+signals essential for cerebellar long-term depression (LTD) at parallel fiber (PF)-Purkinje cell synapses are known to be induced when PF activation precedes climbing fiber (CF) activation by 50-200 ms, consistent with cerebellar learning theories. However, large Ca2+signals and/or LTD can also be induced by massive PF stimulation alone or by photolysis of caged Ca2+or inositol 1,4,5-trisphosphate (IP3). To understand the spike-timing detection mechanisms in cerebellar LTD, we developed a kinetic mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
160
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(190 citation statements)
references
References 58 publications
8
160
1
Order By: Relevance
“…One detailed model of our data (Doi et al, 2005) found that several parameters might be able to shape the timing window, including delays in PF-triggered IP 3 synthesis and degradation of IP 3 . The lifetime of IP 3 elevation has also been suggested to set a time window for coincidence detection in CA1 pyramidal neurons (Nakamura et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…One detailed model of our data (Doi et al, 2005) found that several parameters might be able to shape the timing window, including delays in PF-triggered IP 3 synthesis and degradation of IP 3 . The lifetime of IP 3 elevation has also been suggested to set a time window for coincidence detection in CA1 pyramidal neurons (Nakamura et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with rapid Ca 2ϩ -dependent activation of IP 3 Rs, inactivation induced by Ca 2ϩ has a slow rate of onset (hundreds of milliseconds) and lasts for seconds (Parker and Ivorra, 1990;Finch et al, 1991;Doi et al, 2005). A previous study has shown that repetitive firing of DA neurons produces elevations of [Ca 2ϩ ] i up to ϳ250 nM (Wilson and Callaway, 2000), which may well cause Ca 2ϩ -dependent inactivation of IP 3 Rs.…”
Section: Ip 3 Mediates Differential Regulationmentioning
confidence: 99%
“…Glutamate spillover from bursts of PF signaling activates metabotropic glutamate receptor type 1 (mGluR1) and increases calcium levels through two parallel pathways: extracellular calcium influx from a slow EPSC (sEPSC) (Canepari et al, 2004) and a release of calcium from internal calcium stores (Finch and Augustine, 1998). While calcium release from the internal stores is known to be induced via phospholipase C␤ activation and subsequent inositol trisphosphate production, the mechanism of calcium influx from the extracellular environment is not well understood (Okubo et al, 2004;Doi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%